2010
DOI: 10.1051/0004-6361/200913770
|View full text |Cite
|
Sign up to set email alerts
|

Detection of unidentified infrared bands in a Hαfilament in the dwarf galaxy NGC 1569 with AKARI

Abstract: Context. We report the detection of unidentified infrared (UIR) bands in a filamentary structure associated with Hα emission in the starburst dwarf galaxy NGC 1569 based on imaging and spectroscopic observations of the AKARI satellite. Aims. We investigate the processing and destruction of the UIR band carriers in an outflow from NGC 1569. Methods. We performed observations of NGC 1569 for 6 infrared bands (3.2, 4.1, 7, 11, 15, and 24 μm) with the infrared camera (IRC) onboard AKARI. Near-to mid-infrared (2−13… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…Our result on the detection of the 3.3 μm feature from the halo spectra unambiguously confirms the presence of very small PAHs in the galactic superwind of M 82. With AKARI near-to mid-IR spectroscopy, Onaka et al (2010) also detected the PAH features including the 3.3 μm feature in the filamentary outflow of the starburst dwarf galaxy NGC 1569. Thus, to our knowledge, this is the second clear detection of the PAH 3.3 μm feature in galactic superwind far outside a galactic disk.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our result on the detection of the 3.3 μm feature from the halo spectra unambiguously confirms the presence of very small PAHs in the galactic superwind of M 82. With AKARI near-to mid-IR spectroscopy, Onaka et al (2010) also detected the PAH features including the 3.3 μm feature in the filamentary outflow of the starburst dwarf galaxy NGC 1569. Thus, to our knowledge, this is the second clear detection of the PAH 3.3 μm feature in galactic superwind far outside a galactic disk.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, to our knowledge, this is the second clear detection of the PAH 3.3 μm feature in galactic superwind far outside a galactic disk. Onaka et al (2010) suggested that the PAHs in the filament of NGC 1569 might be produced from the fragmentation of large carbonaceous grains in shocks. Our halo spectra in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The PAH features in galaxy halos seem to have a lower 7.7 µm to 11.3 µm band ratio than that in galactic disks (Irwin & Madden 2006;Galliano et al 2008b). A similar small ratio is also indicated in the interarm region as well as in a filamentary structure associated with the galactic wind (Onaka et al 2010a). The small ratio may be attributed to processing of the band carriers in these tenuous regions or could be related to their formation process.…”
Section: Introductionmentioning
confidence: 62%
“…They may be formed in carbon-rich stars (Galliano et al 2008a;Paradis et al 2008) or in dense clouds (Herbst 1991;Sandstrom et al 2010). Recent observations withAKARI and SOFIA suggest that PAHs are also formed by fragmentation of large carbonaceous grains in shocks associated with a supernova, a galactic wind, or an outflow from a planetary nebula (Onaka et al 2010a;Seok et al 2012;Lau et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we detected galactic outflows of polycyclic aromatic hydrocarbons (PAHs) in the halos of M 82 and NGC 1569 (Yamagishi et al 2012;Onaka et al 2010). We found large variations in the intensity of the aliphatic emission relative to aromatic emission in the galactic superwind regions of M 82 (Yamagishi et al 2012) and the inner galactic bar of NGC 1097 (Kondo et al 2012), indicating systematic changes in the properties of hydrocarbon grains possibly due to large-scale shocks.…”
Section: Uniqueness Of Akari Datamentioning
confidence: 88%